To calculate the distance between the points \((1, 2)\) and \((4, 6)\) using the distance formula \(D = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}\), we can follow these steps:
-
Assign the coordinates:
- \((x_1, y_1) = (1, 2)\)
- \((x_2, y_2) = (4, 6)\)
-
Substitute the coordinates into the formula: \[ D = \sqrt{(4 - 1)^2 + (6 - 2)^2} \]
-
Calculate the differences: \[ D = \sqrt{(3)^2 + (4)^2} \]
-
Square the differences: \[ D = \sqrt{9 + 16} \]
-
Sum the results: \[ D = \sqrt{25} \]
-
Finally, take the square root: \[ D = 5 \]
Therefore, the distance between the points \((1, 2)\) and \((4, 6)\) is \(D = 5\).
So the correct response is: D = 5.